Analisis Dompet Digital “Link Aja Syariah” dari Perspektif Maslahah Mursalah - Anisa Fadilah Zustika; Achmad Fageh (Islamic Economics Journal, 2022)
Industry of 4.0 era it is no stranger to talk about digital wallets whose existence can make it easier for humans to make payment systems.There are many kinds of digital wallets in Indonesia,  first one that is sharia-based is the "Link Aja Syariah" application where this application gets the MUI DSN certificate. The purpose of this study is to analyze the Link Aja Syariah digital wallet application from the perspective of Maslahah Mursalah. The method used in this study uses a qualitative method with a library research approach with primary data sources originating from the official website link aja sharia and secondary data referring to journals, books, ebooks, the Qur'an and hadith and other Islamic literature. Based on the results of the research above, it states that benefits provided by the Link Aja Syariah application were ease of transaction. This benefit can be felt by all, both users and agencies concerned, so that it is in line with the rules of maslaha mursalah.